Lunacy, leprosy and legislation: medical practice and colonial control at the Cape, c. 1820-1831 - Boyd, Michael (Department of Historical Studies, 2017)
This paper examines a series of medical related topics within the context of the Cape Colony in the 1820s. The focus on these specific healthcare issues highlights broader themes in terms of authority, control and power in the governance of the Cape during this period. In addition, the thesis explores the interconnected nature of the Colony within the British Empire and assesses how this position affected standards of treatment and the regulation of the medical profession. The thesis is not intended to be an all-encompassing examination of Cape based health care during the 1820s, however it seeks to highlight a series of interesting cases and their connections to wider trends and notions of authority. The thesis begins by situating the Cape Colony within the wider framework of the Empire during this period. This involves examining characteristics of governance and networks of information that epitomised the era. Having established this broad context, the paper narrows its focus to the specifics of the Cape medical system and how it was supposed to be functioning. Throughout this process a variety of different roles and structures are explored before an in-depth examination of the Cape's place in a medical network is undertaken. How such a structure was utilised is then discussed by looking at specific cases of medical malpractice and negligence. Thereafter, the thesis moves on to look at the Colony's treatment and response to the conditions of 'lunacy' and leprosy within the 1820s. This final chapter uses the focus on these illnesses to act as case studies which underline a number of the themes and factors highlighted in the preceding chapters. As the paper progresses, the inability of both local and metropole officials to exercise influence over the different structures and practitioners of the Cape becomes more and more apparent. This process relies heavily on records from the Cape Town Archive which serve as the cornerstone of the research used in this paper. These are accompanied by contemporary newspaper articles and reports from Commissions' of Enquiry add to this context. From these records a number of interesting micro-historical examples are utilised to speak to general trends, but also indicate spaces in our understanding. The thesis concludes by pointing out the unique nature of medical care and regulation in the Cape context, but also the space for future research.